Frugivory and seed dispersal role of the Yellow-striped Brush-Finch (Atlapetes citrinellus), an endemic emberizid of Argentina - Ruggera, Román Alberto (2014)
The stability and dynamics of multispecies interactions often rely on a small core of species. We examine whether the Yellow-striped Brush-Finch (Atlapetes citrinellus), the only species of bird endemic to the Argentinean Yungas, is a core species for seed dispersal. Of 30 species of fleshy fruit consumed, 16 were dispersed through endozoochory. The Yellow-striped Brush-Finch mostly used the ‘cut or mash’ method of handling fruit, in which reasonably large seeds (>0.04 g) were discarded or swallowed equally. Medium-sized and small seeds were more often swallowed than discarded. Although the fruits consumed were mostly understorey species, there was no difference in the consumption of fruit from forest understorey or canopy when total fruit abundance in vertical strata was considered. By using interaction network metrics, we determined that the role of Yellow-striped Brush-Finches in seed dispersal during the rainy season was more important at higher altitudes and in the southern sector of its distribution. Our findings support the idea that the Yellow-striped Brush-Finch must be considered a core seed-disperser of understorey and canopy fruits. Use of network metrics is an effective way to assess the importance of individual species in a network, allowing restoration and conservation efforts to be focussed on environments in which these species occur.